L’urbanité de l’héritage industriel - Zeila Tesoriere; Renzo Lecardane (In Situ)
At the heart of urban dynamics over the past few decades, the reconversion of riverside and port spaces in cities of the western world is associated with the deindustrialisation of these sites, often situated near historic city centres. This contemporary situation puts industrial heritage conversion at the centre of thinking which goes beyond the mere conservation of the original value of the buildings to question the future of cities, in relation to the notion of sustainability. In New York, after thirty years of neglect, the old railway viaduct known as the High Line has been transformed into an elevated, linear urban parkway. The project can be compared with the Hudson Riverpark, an impressive operation of requalification of the Manhattan riverside, also associated with the older Riverside Park. The High Line is a vestige of the first Industrial Revolution, a hybrid creation suggestive of a flexible morphology mingling infrastructure and building. Its reconversion has succeeded in reactivating growth in an important part of the meatpacking district. The operation brings together local authorities, the New York city administration and landowning companies. In the wake of the regeneration of the east bank of the Manhattan, its reconversion does not follow the dominant model of waterfront regeneration, pioneered in the United States since the 1960s. Through its prism, different political, economic and social relationships can be identified (arrival of Michael Bloomberg as mayor, railway banking, the ‘Friends of the High Line’ association), creating a new approach which has already become a reference. From Chicago to Philadelphia, and not forgetting Rotterdam, many cities now envisage the rehabilitation of vast urban sectors in the same way, by converting their railway viaducts in the manner of the High Line. The importance of this operation allows us to consider deindustrialisation as a process capable of engendering a change in the urban territory through an approach at different scales and crossing over existing boarders.